The United Kingdom - Flint, David, 1946- (Austin, Tex. : Raintree Steck-Vaughn, 1994)
Discusses the geography, population, daily life, industries, environment, and future of Great Britain.
Includes bibliographical references (p. 43) and index.
Keywords: Great Britain -- Juvenile literature; Great Britain